REFLECTING UPON OPENNESS WITHIN GREEK SCHOOL EDUCATIONAL SETTINGS IN THE (POST) PANDEMIC ERA (Proceedings of the International Conference on Education, 2023)
The Covid-19 pandemic outburst combined with the 21st-century globalized society conditions has triggered a wide demand for radical educational changes with an emphasis on the philosophy of openness in order for human rights, equity and democracy to be enhanced. Even though traditional school education seems to be resisting to those changes and maintains its closed character, it was forced to partially modify and readapt its outdated educational practices and policy, due to the imposed lockdowns and the obligatory implementation of distance education. Therefore, this paper adopts a qualitative approach and – by analyzing the textual content of 15 school Minute Books – aims to examine the features of openness and the factors that have influenced it in Greek secondary educational settings during and after the end of the 2021 imposed lockdowns. Findings show that openness in school education is highly affected by several socio-economic and educational factors, such as the existence of vulnerable student groups, educational leadership’s attitude and economic inequalities within the student population. Furthermore, certain openness features have derived in terms of accessibility and flexibility, which are in relation to both distance and face-to-face education. This paper adds up to the existing literature and offers a new insight, as it shows how the worldwide pandemic affected openness in schools, not only during the lockdowns, but also in the aftermath.
Keywords: openness in education; school education; covid-19 pandemic; openness factors; openness features; qualitative content analysis